Knowledge Equity and Open Science in qualitative research – Practical research considerations - Steinhardt, Isabel; Kruschick, Felicitas (Research Ideas and Outcomes)
How can Knowledge In/Equity be addressed in qualitative research by taking the idea of Open Science into account? Two projects from the Open Science Fellows Programme by Wikimedia Deutschland will be used to illustrate how Open Science practices can succeed in qualitative research, thereby reducing In/Equity. In this context, In/Equity is considered as a fair and equal representation of people, their knowledge and insights and comprehends questions about how epistemic, structural, institutional and personal biases generate and shape knowledge as guidance. Three questions guide this approach: firstly, what do we understand by In/Equity in the context of knowledge production in these projects? Secondly, who will be involved in knowledge generation and to what extent will they be valued or unvalued? Thirdly, how can data be made accessible for re-use to enable true participation and sharing?
Keywords: Open Science; Knowledge Equity; Qualitative Methods

Kollaborative Autoethnographien digitaler Praktiken. Eine konzeptionelle, methodische und theoretische Einführung zu einem Lehr-Forschungsprojekt im ersten Corona-Semester - Steinhardt, Isabel (DNGPS Working Paper)
Keywords: Open Science; kollaborative Autoethnographie

Knowledge Equity and Open Science in qualitative research – Practical research considerations - Steinhardt, Isabel; Kruschick, Felicitas (Research Ideas and Outcomes)
How can Knowledge In/Equity be addressed in qualitative research by taking the idea of Open Science into account? Two projects from the Open Science Fellows Programme by Wikimedia Deutschland will be used to illustrate how Open Science practices can succeed in qualitative research, thereby reducing In/Equity. In this context, In/Equity is considered as a fair and equal representation of people, their knowledge and insights and comprehends questions about how epistemic, structural, institutional and personal biases generate and shape knowledge as guidance. Three questions guide this approach: firstly, what do we understand by In/Equity in the context of knowledge production in these projects? Secondly, who will be involved in knowledge generation and to what extent will they be valued or unvalued? Thirdly, how can data be made accessible for re-use to enable true participation and sharing?
Keywords: Open Science; Knowledge Equity; Qualitative Methods

Die (Un-)Sichtbarkeit von (offenen) Bildungsmaterialien in der Soziologie - Hiebl, Johannes; Steinhardt, Isabel; Bigos, Michael (die hochschule)
Der Beitrag beschäftigt sich mit dem Gebrauch von sogenannten Open Educational Resources (OER) innerhalb der deutschsprachigen Soziologie. OER sind Lehr-und Lernmaterialien, die öffent-lich und frei von Kosten zugänglich sind sowie unter einer offenen Lizenz stehen, die es erlaubt, das Material frei zu nutzen, zu vervielfältigen und zu bearbeiten. Um diese Form der Bereitstellung von Lehr-und Lernmaterial zu fördern, sind im deutschen Sprachraum in den letzten Jahren verschie-dene digitale Infrastrukturen entstanden, die an einzelnen Hochschulstandorten, aber auch hochschulübergreifend Lehrenden zur Verfügung stehen, um dort ihr Material zu veröffentlichen. Es wurden 37 dieser Repositorien untersucht. Darüber hinaus wurde auch die Videoplattform YouTube nach soziologischem Lehr-und Lernmaterial durchforstet. Der Beitrag stellt den Zeitverlauf und die Akteur:innen der OER-Veröffentlichungen dar. Anschließend soll mithilfe eines praxistheoretischen Vokabulars die Lehre innerhalb der Soziologie aufgeschlüsselt und ein möglicher Bezug zu den empirischen Ergebnissen hergestellt werden.
Keywords: Soziologie; Praxistheorie; Repositorien; Open Educational Resources; OER

Dem eigenen Anspruch auf der Spur - Ternes, Doris; Bernhard, Nadine; Gewinner, Irina; Goller, Antje; Lohner, David; König, Karsten; Röwert, Ronny; Steinhardt, Isabel; Thielsch, Angelika (Hochschulen in der Pandemie. Impulse für eine nachhaltige Entwicklung von Studium und Lehre)
Der Beitrag geht der Frage nach, welchen Herausforderungen Lehrende durch die digitale Lehre im ersten Corona-Semester 2020 begegnet sind und welche Strategien sie für deren Bewältigung gewählt haben. Als Datengrundlage dienendazu sechs autoethnographische Stories, entstanden im Projekt AEDiL. Diese haben sich als wertvolles Material erwiesen, um unmittelbare Einblicke in das Lehrhandeln und die -planung zu erhalten und die weiterführende Analyse zu ermöglichen. Dabei offenbarte sich der gemeinsame Anspruch der studierenden-zentrierten Lehre als wiederkehrendes Muster. Die mehrstufige Analyse legt offen, wie Lehrpersonen mit den Themen Beziehungsaufbau, Schaffung eines (digitalen) Raums sowie Sicherheit für Studierende umgehen und sich daraus Handlungsmuster entwickeln.

(Be)Werten im organisationsabhängigen Interaktionssystem: das Beispiel Peer Review in Akkreditierungsverfahren von Hochschulen und Studiengängen - Schneijderberg, Christian; Götze, Nicolai; Steinhardt, Isabel; Schindler, Janosch (Zeitschrift für Evaluation)
In diesem Beitrag wird die ‚What Works‘-Debatte in der Sozialen Arbeit um die zentrale Frage nach Wirkfaktoren erweitert. Der empirische Nachweis von Wirkfaktoren in sozialarbeiterischen Interventionen ist bis heute ein Desiderat. Vor dem Hintergrund der Realist Evaluation werden in diesem Beitrag relevante Wirkfaktoren (Kontexte und Mechanismen) herausgearbeitet. Datengrundlage stellt eine Onlinebefragung von 200 fallführenden Fachpersonen in vier sozialarbeiterischen Handlungsfeldern in der deutschsprachigen Schweiz dar (Arbeitsintegration, Bewährungshilfe, Schuldnerberatung, Sozialhilfe). Die Ergebnisse verweisen auf signifi kante Wirkfaktoren von erfolgreichen Interventionen, u.a. Arbeitsstile der Fachpersonen und Verhaltensmerkmale der Klient(inn)en und können in einem allgemeinen Wirkungsmodell mit handlungsfeldübergreifenden Outcomes verdichtet werden. Diese Erkenntnisse leisten einen Beitrag zur Professionalisierung der Sozialen Arbeit sowie zur Konstruktion von Wirkungsmodellen und sollen zukünftige weitere Forschungsvorhaben in diese Richtung anregen.
Keywords: Soziologie des Wertens und Bewertens; Peer Review; Akkreditierung; Hochschule

Eingeschrieben und Geblieben. Herkunftsgruppenspeziﬁsche Bedingungen des Studienverbleibs nach der Studieneingangsphase an Universitäten. - Mauermeister, Sylvi
Hochschulische Bildungsverläufe und -erfolge sind in Deutschland anhaltend maßgeblich von der sozialen Herkunft beeinflusst. Gleichzeitig bestehen Anforderungen an moderne Gesellschaften, Unterschiede in den bildungsbezogenen Chancen abzuschaffen, die nicht aus Leistungsunterschieden, sondern aus der Zugehörigkeit zu bestimmten sozialen Gruppen resultieren. Auch angesichts der hohen Bedeutung der Studieneingangsphase für den Studienerfolg stellt sich die Frage, wie sich Unterschiede in den ökonomischen und kulturellen Ressourcen der Herkunftsfamilie auf den Verlauf der Studieneingangsphase auswirken. Welche Unterschiede zeigen sich in den Bedingungen des Studienverbleibs, der Ausstattung mit studienverbleibsrelevanten Ressourcen und dem Umgang mit Problemen? Die Untersuchung zeigt vor allem zweierlei: Zum einen sind die Schwierigkeiten mit den universitären und fachspezifischen Bedingungen, die bereits nach dem ersten Studiensemester sichtbar werden, stark abhängig von der Fächergruppe, in der studiert wird. Zum anderen ist für das Gelingen der Studieneingangsphase das kulturelle Kapital der Herkunftsfamilie von größerer Bedeutung als das ökonomische Kapital. Die Ergebnisse sind gleichermaßen für die Bildungs- wie die Ungleichheitsforschung relevant und erlauben es, Handlungsoptionen zur Gestaltung der Studieneingangsphase abzuleiten.

Paralleluniversen des Wissenschaftsmanagements: Ein Vergleich zwischen Hochschulen und außeruniversitären Forschungseinrichtungen. - Schneider, Sebastian; Mauermeister, Sylvi; Aust, Robert; Henke, Justus

Von lebenden Systemen und gefühlten Zahlen. Eine körpersoziologische Analyse des finanzaufsichtlichen Risikobewertungsregimes - Knoll, Lisa (Österreichische Zeitschrift für Soziologie)
Der hier vorliegende Beitrag erarbeitet Verbindungslinien zwischen Wirtschaftssoziologie (insb. Finanzsoziologie), Soziologie der Bewertung und Körpersoziologie anhand des Falls finanzmarktregulatorischer Risikobewertung. Dabei spielt der analytische Begriff der Prothese (Michel Callon) eine wichtige Rolle. Nach der Finanzkrise kommt es zu einer Neuverteilung von sensorischen Bewertungskompetenzen in einer hierarchisch aufgebauten, vernetzten Wissensarchitektur. Es ist nun die Maschine, der Lebendigkeit attestiert wird, während der Mensch parzellierte Funktionen in einer Apparatur übernimmt. Gleichzeitig soll der Mensch so zu einem adäquaten und beweglichen (spielerischen) Umgang mit Risiken angeregt werden, die man ihm/ihr in einem eher groben und einfachen Aufsichtssystem nicht mehr zutraute (hier wurden „regulatory arbitrage“ und „kreative Buchführung“ zum Problem). Der Aufsatz rekonstruiert die praktischen Orientierungen und kollektiven Erfahrungen dieses finanzaufsichtlichen Umbaus anhand zweier problemzentrierter Interviews. Unter Rekurs auf die Körperbezüge in diesen Interviews wird die Paradoxie eines Systems herausgearbeitet, das nach wie vor auf individuelle Entscheidungsrationalität und -agilität setzt, diese nun aber maschinell zu erschaffen sucht.
Keywords: General Social Sciences

Contested Social Impact Bonds: welfare conventions, conflicts and compromises in five European Active-Labor Market Programs - Fraser, Alec; Knoll, Lisa; Hevenstone, Debra (International Public Management Journal)
Keywords: Public Administration; Business and International Management

Die EU-Taxonomie für nachhaltige Finanzen: Auf dem Weg in den grünen Kapitalismus? - Knoll, Lisa (Kapitalismus und Nachhaltigkeit)
Keywords: Klima

Lehrer*innenbilder in Autosozioanalysen. Die Emergenzfunktion von Lehrer*innen als abwesende Dritte - Haker, Christoph; Otterspeer, Lukas (Bilder von Lehrer*innenberuf und Schule (Mediale) Entwürfe zwischen Produktion, Rezeption und Aneignung)

Grenzbearbeitungen – methodologische Überlegungen zu einer sozialwissenschaftlichen Forschungsperspektive - Haker, Christoph; Otterspeer, Lukas (Grenzen auflösen – Grenzen ziehen: Grenzbearbeitungen zwischen Erziehungswissenschaft, Politik und Gesellschaft)

Antiakademismus heute - Haker, Christoph; Otterspeer, Lukas; Schildknecht, Lukas (Demokratie unter Druck)

Have Academics’ Citation Patterns Changed in Response to the Rise of World University Rankings? A Test Using First-Citation Speeds - Lee, Soo Jeung; Schneijderberg, Christian; Kim, Yangson; Steinhardt, Isabel (Sustainability)
Academics may actively respond to the expectations of the academic status market, which have largely been shaped by the World University Rankings (WURs). This study empirically examines how academics’ citation patterns have changed in response to the rise of an “evaluation environment” in academia. We regard the WURs to be a macro-level trigger for cementing a bibliometric-based evaluation environment in academia. Our analyses of citation patterns in papers published in two higher education journals explicitly considered three distinct periods: the pre-WURs (1990–2003), the period of WURs implementation (2004–2010), and the period of adaption to WURs (2011–2017). We applied the nonparametric Kaplan–Meier method to compare first-citation speeds of papers published across the three periods. We found that not only has first-citation speed become faster, but first-citation probability has also increased following the emergence of the WURs. Applying Cox proportional hazard models to first-citation probabilities, we identified journal impact factors and third-party funding as factors influencing first-citation probability, while other author- and paper-related factors showed limited effects. We also found that the general effects of different factors on first-citation speeds have changed with the emergence of the WURs. The findings expand our understanding of the citation patterns of academics in the rise of WURs and provide practical grounds for research policy as well as higher education policy.
Keywords: world university rankings; citation; first-citation speed; Minerva; Studies in Higher Education

Students in the spotlight: Using collaborative autoethnography to build a community of learning in the Corona crisis - Steinhardt, Isabel (ISA Pedagogy Series)
Due to the Corona crisis, German Higher Education Institutions had to close their campuses in March and lecturers had to teach online. To understand how the Corona crisis affected students, first this article explains the structural and social inequalities in the German higher education system, using Tinto's (1975; 1997) student engagement theory. Second, the concept of Bergman-Rosamond et al. (2020) is used to analyze the challenges that Corona has raised for students, including current surveys. We found that the closure of the social space campus (and the Corona crisis as a whole) particularly hit hard those students who had previously been affected by (intersectional) inequality. Therefore, to lessen the specific challenges associated with the ad hoc transition to digital studying, the creation of a digital community of learning can help. We demonstrate how such a community can be created by the example seminar, "Digital practices: an autoethnographic observation". During the seminar, students recorded their digital technology use in a journal, and we analyzed the diary entries using the collaborate autoethnography method. The seminar example shows that this method is well suited for the development of a community of learning as it not only places students in the spotlight but as students work together on a topic they get to know each other, and a basis of trust is created through peer-feedback. Therefore, it was important to have a digital space (in this case Mahara) where the exchange could take place. The continuous insight into the students’ "learning status" enabled the lecturer to promote the learning and provide individual assistance for the students.
Keywords: Intersectionality; inequality; gender; diversity; higher-education; crisis

Opening up and Sharing Data from Qualitative Research: A Primer - Steinhardt, Isabel; Fischer, Caroline; Heimstädt, Maximilian; Hirsbrunner, Simon David; Ikiz-Akinci, Dilek; Kressin, Lisa; Kretzer, Susanne; Möllenkamp, Andreas; Portzelt, Maike; Rahal, Rima-Maria; Schimmler, Sonja; Wilke, René; et al.
The call for free access to research data and materials is becoming louder and louder from the political and scientific communities in Germany. More and more researchers are facing demands to open up qualitative research data for scientific purposes. They often have a general interest in sharing their data, but are unsure how to proceed. This handout was developed to provide an initial introduction to opening and sharing qualitative data. It was developed at a workshop held in Berlin in January 2020, organized by the research group „Digitization of Science“ of the Weizenbaum Institute, together with its associate researcher Dr. Isabel Steinhardt from the University of Kassel. The workshop involved staff from German research data centers as well as mentees and mentors from the Fellow Program Open Science who already have experience with Open Science, qualitative research, and interdisciplinary research. The handout is addressed primarily to qualitatively researching scientists in Germany. For this reason, it was initially written in German. One year later, we have now decided to translate the handout into English as well. The reasons are twofold: first, we want to make it accessible to researchers in Germany with little knowledge of German. Second, we also want to give interested people outside Germany an insight into the German system and the German discussion about opening up and sharing qualitative data. Due to the objectives and the history of its development, the handout focuses on the German context. This includes the literature references and further sources, and the references to research data centers as well as legal issues. We have deliberately not included a contextualization of the German situation in international discussions in order to keep the handout as short as possible.

Nachhaltigkeitsmärkte im Vergleich. Zur Transformation von Staatlichkeit - Knoll, Lisa (Der Staat in der Großen Transformation)

Bewerten und Prüfen. Zur Relevanz der Figur der Prüfung für die Organisationssoziologie - Knoll, Lisa (Organisation und Bewertung)

Grenzüberschreitung und Distanzierung – Geschlechterforschung in universitären Toiletten - Krollmann, Rabea; Schmidt, Rebecca; Spill, Annika (blog interdisziplinäre geschlechterforschung)